Sterile activation of invariant natural killer T cells by ER-stressed antigen presenting cells - Bedard, M (2019)
Invariant NKT (iNKT) cells are a subset of innate-like lymphocytes that recognize lipid antigen presented on monomorphic CD1d molecules. These cells have the unique ability to shape immunity during anti-tumour immune responses and other forms of sterile and non-sterile inflammation. Recent studies have highlighted a variety of classes of endogenous and pathogen-derived lipid antigens that can trigger iNKT cell activation under sterile and non-sterile conditions. However, the context and mechanisms that drive the presentation of self-lipid antigens in sterile inflammation remain unclear. Given that ER-stress is prevalent during tumourigenesis coupled with the intersection between the ER-stress pathways and lipid metabolism, we hypothesized that ER-stressed CD1d+ cells might present immunogenic self-lipid(s) on CD1d molecules to activate iNKT cells in sterile conditions. We demonstrate that ER-stressed dendritic cells activated iNKT cells in a CD1d-dependent manner, which in turn promotes dendritic cell maturation. We illustrate that PERK signalling increases CD1d-mediated presentation of immunogenic endogenous lipid species. We demonstrate that the immunogenic self-lipid(s) are likely ceramide-based and loaded onto CD1d in the endosomal/lysosomal compartments. We also investigate the relevance of this mechanism in a human tumour setting by analysing iNKT cell responses to multiple myeloma cell lines and identifying ER-stressed myeloid cells in the tumour microenvironment. In conclusion, this work defines a previously unidentified mechanism that controls iNKT cell activation during sterile inflammation, with a potential role in human health and disease.